2020
DOI: 10.1155/2020/1363212
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Hydrothermal Synthesis of N, Fe-Codoped Carbon Dots as Mimic Peroxidase and Application on Hydrogen Peroxide and Glucose Detection

Abstract: In this paper, N, Fe-codoped carbon dots (N, Fe-CDs) were synthesized from β-cyclodextrin, ethylenediamine, and ferric chloride for the first time using a convenient one-step hydrothermal method. The obtained N, Fe-CDs were characterized by various methods including transmission electron microscopy, X-ray photoelectron spectroscopy, and Fourier-transform infrared spectroscopy. The N, Fe-CDs exhibited better catalytic activity than horseradish peroxidase (HRP) and caused an evident color change for 3,3′,5,5′-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Doping various elements is an effective method to adjust the electronic structure and surface chemical reactivity of CDs. 43,58 Studies have shown that nitrogen-doped CDs have good antibacterial activity. They produce ROS in bacterial cells by simulating the activities of POD-like enzymes and OXD-like enzymes, thus killing bacteria in a short time.…”
Section: Nanozymes Activity Modulationmentioning
confidence: 99%
“…Doping various elements is an effective method to adjust the electronic structure and surface chemical reactivity of CDs. 43,58 Studies have shown that nitrogen-doped CDs have good antibacterial activity. They produce ROS in bacterial cells by simulating the activities of POD-like enzymes and OXD-like enzymes, thus killing bacteria in a short time.…”
Section: Nanozymes Activity Modulationmentioning
confidence: 99%
“…Li et al synthesized N,Fe-codoped carbon quantum dots (N,Fe-CQDs) using β-CD, ferric chloride, and ethylenediamine through a convenient one-step green hydrothermal route . The N,Fe-CQDs revealed higher catalytic activity in comparison with horseradish peroxidase (HRP), which produced an apparent color change in the presence of H 2 O 2 for 3,3′,5,5′-tetramethylbenzidine.…”
Section: Cyclodextrin-based Gm Sensorsmentioning
confidence: 99%
“…(A) Selectivity of N- and Fe-CQDs in the presence of different compounds and (B) the comparison of their absorbance intensity. Reprinted with permission from ref . Copyright © 2020.…”
Section: Cyclodextrin-based Gm Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanozymes are composed of nanoparticles of inorganic materials possessing intrinsic enzymatic activities. Nanozymes have been developed with nanoparticle forms of Fe 3 O 4 , [ 16 ] platinum, [ 108 ] gold, [ 109,110 ] copper oxide, [ 111 ] CoFe 2 O 4 , [ 112 ] graphene oxide, [ 113 ] carbon, [ 114 ] among others. Besides classifying the nanozymes based on the type of enzymatic reactions they mimic, [ 115 ] they may also be categorized based on their atomic composition, which largely determine their catalytic activity and specificity in operation.…”
Section: Nanozymesmentioning
confidence: 99%